Bilateral Macrodactyly of the Halluces in an Adolescent Girl Corrected with Shortening Osteotomies of the First Metatarsal and the Phalangeal Bones: A Case Report. Issue 3 (July 2018) - Kalb, Juan Pedro; Suarez, David Andrés; Herrera, Ana Milena
Abstract : Case: A 14-year-old girl presented with painful high-arched feet and unusual, asymptomatic, bilateral macrodactyly of the halluces. After a year of observation, a surgical reduction was performed because of the psychological effect that the abnormality had on the patient. Bilateral shortening osteotomies of the metatarsal and the proximal phalangeal bones were performed. At 2 months after surgery, complete bone healing and alignment had been achieved. At the 5-year follow-up, we noted fully functional big toes, plantigrade feet, bilateral proper toe formula, and extreme patient satisfaction with the cosmetic results. Conclusion: Dual osteotomies for toe shortening in a patient with bilateral nondysmorphic macrodactyly provided appropriate length reduction and satisfactory aesthetic and functional results.